2003
DOI: 10.1017/s0025315403008737
|View full text |Cite
|
Sign up to set email alerts
|

Body shape and trawl cod end selectivity for nine commercial fish species

Abstract: This study investigates the catch components of a commercially used demersal trawl cod end in Izmir Bay, and reveals some of the morphological characteristics of nine commercial ¢sh species; red mullet (Mullus barbatus), hake (Merluccius merluccius), whiting (Merlangius merlangus euxinus), poor cod (Trisopterus minutus capelanus), tub gurnard (Trigla lucerna), common pandora (Pagellus erythrinus), axillary sea bream (Pagellus acarne), picarel (Spicara smaris) and annular sea bream (Diplodus annularis) in relat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
49
0
3

Year Published

2010
2010
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(59 citation statements)
references
References 2 publications
7
49
0
3
Order By: Relevance
“…Available studies have revealed differences in the demersal assemblages between these regions (Tsimenides et al 1991, Kallianiotis et al 2000, Labropoulou and Papaconstantinou 2000, Klaoudatos et al 2010 Thanks to increased research effort in the southern and northwestern region of the Aegean, information on the demersal fisheries and their impact on ecosystems has improved substantially (e.g. Petrakis and Stergiou 1997, Smith et al 2000, Labropoulou and Papaconstantinou 2004, Damalas and Vassilopoulou 2011, Maravelias et al 2012, Damalas et al 2010, Tosunoğlu et al 2003a, 2003b, Tokaç et al 1998. Similarly, demersal fish communities of the northeastern Aegean have also been studied and compared with other areas (Labropoulou and Papaconstantinou 2000, Keskin et al 2011a, 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…Available studies have revealed differences in the demersal assemblages between these regions (Tsimenides et al 1991, Kallianiotis et al 2000, Labropoulou and Papaconstantinou 2000, Klaoudatos et al 2010 Thanks to increased research effort in the southern and northwestern region of the Aegean, information on the demersal fisheries and their impact on ecosystems has improved substantially (e.g. Petrakis and Stergiou 1997, Smith et al 2000, Labropoulou and Papaconstantinou 2004, Damalas and Vassilopoulou 2011, Maravelias et al 2012, Damalas et al 2010, Tosunoğlu et al 2003a, 2003b, Tokaç et al 1998. Similarly, demersal fish communities of the northeastern Aegean have also been studied and compared with other areas (Labropoulou and Papaconstantinou 2000, Keskin et al 2011a, 2011b.…”
Section: Introductionmentioning
confidence: 99%
“…They estimated that fork lengths of the fish in age group I-II-III as 10.3, 13.4, and 15.4 cm, respectively. These values were converted to total length by using conversion formulation given by Tosunoğlu et al (2003b) and total lengths for age groups I, II, and III were calculated as 11.7, 15.2 and 17.5 cm, respectively. The populations entering to the codend in this study show a similar age distribution to the findings of Kınacıgil et al (2001).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that the selectivity of diamond mesh codend used commercially (nominal 40 mm or 44 mm diamond) by Turkish demersal trawlers is rather poor (Özbilgin & Tosunoğlu, 2003;Tosunoğlu, Özbilgin & Tokaç, 2003a;Tosunoğlu, Doğanyilmaz & Özbilgin, 2003b;Tokaç, Özbilgin & Tosunoğlu, 2004). Turkish Fisheries Regulations (TFR) allow trawlers to use a minimum of 40 and 44 mm codend diamond mesh size in the Black Sea and the remain Turkish waters, respectively.…”
Section: Introductionmentioning
confidence: 99%